Identifying the site for intercostal catheter insertion in the emergency department: Is clinical examination reliable?. (11th September 2014) - Carter, Peter; Conroy, Sheree; Blakeney, Jade; Sood, Bimal
Abstract Objective To determine whether ED doctors, comprising both consultants and registrars, can accurately identify the 4th or 5th intercostal space (ICS), commonly used for intercostal catheter insertion. Methods An observational study was designed using a sample of ED doctors applying their clinical skills to a convenience sample of patients reflecting a heterogeneous mix of ED patients. Patients already receiving a CXR in our ED were examined by a registrar or consultant who placed a radiopaque marker on the patients' chest wall over the site they determined to be the 4th or 5th ICS. Consultant radiologists reported the marker's position from postero‐anterior projection CXRs, and results were analysed comparing consultants with registrars, right to left hemithoraces and male to female patients. Results ED doctors participating in the present study placed the marker over the 4th or 5th ICS 36.2% of the time, with no significant difference between consultant and registrar groups, nor right or left hemithoraces. Accuracy was improved in female patients compared with male patients. Conclusion Emergency registrars and consultants sampled from a regional ED appeared unable to reliably identify the 4th or 5th ICS, as evidenced by marker position, in a heterogeneous patient population.